Effect of fibreoptic bronchoscopy on pulmonary function. Issue 1 (January 1990) - Peacock, A J; Benson-Mitchell, R; Godfrey, R
Abstract : Several studies have shown that after fibreoptic bronchoscopy there may be a deterioration in lung function but it is not known whether this is due to the premedication, the topical anaesthetic, or the obstruction produced by the bronchoscope. The effects of each part of the procedure on spirometric measurements were studied in patients with lung disease and in normal non-smokers. Measurements were made after premedication (papaveretum and atropine) in seven patients and after topical anaesthesia of the bronchial tree (340 mg lignocaine) with and without the bronchoscope in the trachea in 21 patients and 10 control subjects. Premedication had no effect. In the normal subjects lignocaine produced significant falls in FEV1, forced vital capacity (FVC), peak expiratory flow (PEF), and peak inspiratory flow (PIF), and insertion of the bronchoscope caused further falls that were also significant. In the patients, however, although anaesthesia produced significant falls in FEV1, FVC, PEF, and PIF of similar magnitude to those found in the normal subjects, there was no further important decrease when the bronchoscope was inserted. It is concluded that the major effect of bronchoscopy on lung function is due to topical lignocaine in the airways, and in patients with lung disease (excluding asthma or a central obstructing carcinoma) the insertion of the bronchoscope causes little additional obstruction.